Acute ischemic proctitis in a patient with factor V Leiden – a clinical case - Ribeiro, Rómulo; Fernandes, Jorge; Silva, Miguel; Serrão, Goreti; Cruz, Pinto da; Teixeira, Aires (Revista Portuguesa de Cirurgia, 2012)
Acute ischemic proctitis is a rare pathologic condition. Resistance to activated protein C due to factor V Leiden mutation is the single most common cause of hereditary thrombophilia, although a rare cause of ischemic colitis. The authors present a clinical case of acute ischemic proctitis attributable to resistance to activated protein C due to factor V Leiden mutation. This case report illustrates the difficulties in making the clinical distinction between ischemic proctitis and other pathologic entities. The literature on the subject is reviewed. Keywords: Ischemic proctitis – Factor V Leiden – Surgical treatment